Deiksis pada Berita KPK Ungkap Kasus Riza Chalid di Kompas.com - Hanifah Annisa Salsabila; Hildansyah, Irdan; Dedi Supriadi; Rohanda, Rohanda (MUKASI: Jurnal Ilmu Komunikasi, 2026)
This study analyzes the use of deixis elements in the news "KPK Reveals Riza Chalid's Connection with the Corruption Suspect in the Procurement of Catalysts" published by Kompas.com on October 22, 2025, using Stephen C. Levinson's (1983) deixis theory, which includes personal, spatial, temporal, social, and discourse deixis. This study uses a qualitative descriptive method with a listening and note-taking technique to identify linguistic data that appears in the text. The results show that deixis in the news not only functions as a linguistic reference marker, but also as a pragmatic device that plays a role in forming the context and framing of information. Personal deixis is used to indicate the position of participants and maintain the objectivity of journalistic narratives, while spatial and temporal deixis function to clarify the location, time, and chronology of events so that the information is presented coherently and easily followed. Social deixis is seen through the use of titles, positions, and forms of address that reflect the hierarchy and power relations between law enforcement agencies and the parties reported on. Meanwhile, discourse deixis plays a role in maintaining text cohesion and coherence through linking sentences and sections. This finding confirms that the choice of deictic forms in news texts has significant pragmatic implications in shaping the construction of meaning and influencing readers' perceptions of reported legal events. Thus, deictic analysis can be an important instrument for understanding how the media constructs reality through language.